Concrete technology – towards better environmental sustainability / Wan Akmal Zahri Wan Zaharuddin and Wan Abdullah Wan Alwi - Wan Zaharuddin, Wan Akmal Zahri; Wan Alwi, Wan Abdullah (2012)
Concrete is a widely used construction material throughout the world and it is still in demand for future development of infrastructures. Extensive usage of concrete lead to huge consumption of non-renewable natural resources and energy; it is also responsible for emitting large amounts of carbon dioxide into the atmosphere which contributes to global warming. However, recent development in concrete technology has focused more towards environmentally friendly and sustainable practices. This paper reviews emerging concrete technology that will lessen the environmental effects of concrete usage such as the use of cement substitute materials (fly ash, rice husk ash, ground granulated blast furnace slag), and alternative aggregates from various industrial by-products. Other related technologies that could contribute to sustainable concrete industry are identified. Barriers in implementing the new emerging environmentally friendly concrete technologies are discussed such as the regulatory code of practices and various concrete standards and specifications. More research for better understanding of new concrete technology and tighter collaboration between researchers and regulatory bodies are needed to expedite the use of new concrete technologies which are more environmentalyl friendly by reducing natural resources consumption, energy and carbon dioxide emission.